Die Mount Coke-sendingstasie en eerw. J.W. Appleyard se Xhosa-Bybelvertaling (Historia, 2021)
-
Keywords: Methodist missionaries; Appleyard; J.W.; Mount Coke-mission; Missions; Xhosa; Bible translation